2021
DOI: 10.3390/cancers13205104
|View full text |Cite|
|
Sign up to set email alerts
|

Opposite Incidence Trends for Differentiated and Medullary Thyroid Cancer in Young Dutch Patients over a 30-Year Time Span

Abstract: Thyroid cancer is the most common endocrine malignancy in children. A rising incidence has been reported worldwide. Possible explanations include the increased use of enhanced imaging (leading to incidentalomas) and an increased prevalence of risk factors. We aimed to evaluate the incidence and survival trends of thyroid cancer in Dutch children, adolescents, and young adults (0–24 years) between 1990 and 2019. The age-standardized incidence rates of differentiated thyroid cancer (DTC, including papillary and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…However, in terms of percentage, the proportion of high-risk cases appeared to be higher in the pre-school group than that in the school-age group. Therefore, young age serves as a critical risk factor in the T stage and ATA risk level of DTC in children, which has some similarities to another large retrospective cohort study by Lebbink et al (5). Positive physical examination and ultrasonic examination should be attached of importance for the early diagnosis and treatment of DTC in pre-school children.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…However, in terms of percentage, the proportion of high-risk cases appeared to be higher in the pre-school group than that in the school-age group. Therefore, young age serves as a critical risk factor in the T stage and ATA risk level of DTC in children, which has some similarities to another large retrospective cohort study by Lebbink et al (5). Positive physical examination and ultrasonic examination should be attached of importance for the early diagnosis and treatment of DTC in pre-school children.…”
Section: Discussionmentioning
confidence: 66%
“…Symptoms in children are atypical at initial diagnosis, so thyroid cancer is often diagnosed in an advanced stage or after the peripheral invasion and distant metastases. Previous studies have confirmed that the range of tumor invasion is more extensive, as is often the case, the rate of distant metastases and locoregional relapse is higher in DTC children than adults (4,5). Fortunately, mortality after thyroidectomy in well-differentiated pediatric individuals is very low (6,7).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…This hypothesis is further supported by the much higher incidence of the condition in females aged 15–19 years old compared to females aged 10–14 years old. However, Lebbink et al [ 18 ] found a female predominance in differentiated TC even in prepubertal girls < 10 years old, who had not been exposed to a surge of estrogen levels yet. This finding is controversial, since the vast majority of recent works claimed that increased age results in an increasingly disproportionate number of females affected compared to their male peers, with nearly a 6:1 ratio by 15–19 years of age [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the original article [ 1 ], there was a mistake in Figure 1 as published. In this figure, two years are missing (2000 and 2001).…”
mentioning
confidence: 99%